2021
DOI: 10.3390/diagnostics11030575
|View full text |Cite
|
Sign up to set email alerts
|

Optical Devices in Tracheal Intubation—State of the Art in 2020

Abstract: The review article is focused on developments in optical devices, other than laryngoscopes, in airway management and tracheal intubation. It brings information on advantages and limitations in their use, compares different devices, and summarizes benefits in various clinical settings. Supraglottic airway devices may be used as a conduit for fiberscope-guided tracheal intubation mainly as a rescue plan in the scenario of difficult or failed laryngoscopy. Some of these devices offer the possibility of direct end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 111 publications
0
9
0
Order By: Relevance
“…The visible stylet for tracheal intubation has been employed since the 1980s. Since then, different types of visible stylets have been approved to facilitate tracheal intubation [ 14 ]. Slight differences exist between these stylets.…”
Section: Discussionmentioning
confidence: 99%
“…The visible stylet for tracheal intubation has been employed since the 1980s. Since then, different types of visible stylets have been approved to facilitate tracheal intubation [ 14 ]. Slight differences exist between these stylets.…”
Section: Discussionmentioning
confidence: 99%
“…These devices include, but are not limited to, hybrid devices, optical stylets, single-use fiberscopes, and fiberoptic tracheal tubes. Although well-designed randomized clinical trials (RCTs) are limited, the efficacy of these new technologies have been reported in various studies including case series and cohort studies [ 6 ]. However, in the pediatric population, direct laryngoscopy is still the mainstream tool of tracheal intubation for surgical procedures, while video laryngoscopy (VL) is increasingly popular and used successfully in difficult airway situations [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…During perioperative intubation, difficult airways show a relatively low incidence (4.4%) ( 3 ), slightly increased (4.7%) for critically ill patients ( 4 ). The development of new airway devices ( 5 ), the publication of national and international airway management guidelines and the possibility of improving technical and non-technical skills based on simulation scenarios contribute to the reduction of severe airway management complications. Nevertheless, closed claims analysis shows a decrease of adverse events occurring during general anesthesia induction, while no decreases are observed during the maintenance or extubation phase ( 6 ).…”
Section: Introductionmentioning
confidence: 99%